2008
DOI: 10.1089/dia.2007.0280
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Magnetic Field on the Biomechanics Parameters of Soleus and Extensor Digitorum Longus Muscles in Rats with Streptozotocin-Induced Diabetes

Abstract: In our study, these results suggest that MF exposure regulates the isometric contractile characteristics of the soleus and EDL muscles of rats with diabetes, positively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…In addition, the CT and HRT of the rats in group DM were found to be prolonged compared to group C ( p < 0.05). On the other hand, the maximal tetanic force values obtained from skeletal muscles for the groups treated with antioxidant treatment increased significantly ( p < 0.05) in comparison with group DM and group C. We observed that tetanic contraction forces improvement was 3-4 times greater than the isometric contraction force, which correlates with the results from our previous study [ 17 , 36 ].…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the CT and HRT of the rats in group DM were found to be prolonged compared to group C ( p < 0.05). On the other hand, the maximal tetanic force values obtained from skeletal muscles for the groups treated with antioxidant treatment increased significantly ( p < 0.05) in comparison with group DM and group C. We observed that tetanic contraction forces improvement was 3-4 times greater than the isometric contraction force, which correlates with the results from our previous study [ 17 , 36 ].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the blood glucose levels for diagnosing diabetes in humans during fasting and 2 h postprandial are 7.0 mmol/L (126 mg/dL) or greater and 11.1 mmol/L (200 mg/dL) or greater [28] , respectively, and the situation for diabetic rats is that they can be considered as diabetic with blood glucose levels of 300 mg/dL (16.7 mmol/L) [7] . The J48 algorithm used the Twitch (mN/mm 2 ) feature to classify the data in the set.…”
Section: Resultsmentioning
confidence: 99%
“…Experimentally induced diabetes is associated with changes in the contractile and electrical properties of skeletal muscles. The soleus and extensor digitorumlongus (EDL) are important skeletal muscles that play important roles in standing to the gravity force and exercises [7] . At the same time, atrophy may develop (muscle loss) in skeletal muscles and results in decreased muscle strength.…”
Section: Introductionmentioning
confidence: 99%
“…In muscle cells, SERCA promotes relaxation by pumping calcium ions from the cytosol into the lumen of the SR, the main storage compartment for intracellular calcium (Primeau et al, 2018). In another study that investigated the effect of MF on the isometric contraction properties of soleus and extensor digitorum longus muscles in rats, it has been reported that MF increases both muscle contraction forces compared to control values (Pelit et al, 2008). Also, MF decreased the contraction time of the two muscles of rats.…”
Section: Discussionmentioning
confidence: 99%